A survey of the educational resources of the City of Dagupan - Ceralde, Nemesio 1904- ([Quezon City University of the Philippines], 1954)
This study presents a survey of the educational resources of the city of Dagupan. It includes facts and figures about the educational institutions, both public and private, and the mass media.
Bibliography: p. 286-289.
Thesis (M.Ed.)--University of the Philippines, 1954
Typewritten
Vita
Keywords: Education -- Pangasinan -- Dagupan